Being an Informal Caregiver of a Person with a Pressure Ulcer in the Azores Islands. (October 2015) - Rodrigues, Alexandre M.; Ferré-Grau, Carmen; Ferreira, Pedro L.
ABSTRACT OBJECTIVE: This study aimed at both understanding the experience of informal caregivers of people with pressure ulcers (PrUs), as well as perceiving the relevant aspects of the narratives emerging from the experience of those caregivers. DESIGN: A qualitative, exploratory, grounded-based theory data analysis was implemented. The authors used NVivo 9 software (QSR International Inc, Burlington, Massachusetts) on semistructured interviews. PARTICIPANTS: The study participants were 9 informal caregivers of people with PrUs. RESULTS AND DISCUSSION: An individual's personal characteristics, the person he or she is caring for, and social pressure are typically the primary reasons to be a caregiver. In fact, PrUs require specific care associated with an impact on caregivers at different levels, including changes in everyday life, needs and feelings emerging from the care they provide, quality of life conditioned by their professional status, and burdens induced by physical and emotional demands. Oftentimes, family members and external entities—with emphasis on the nursing team—provide support to the caregiver. Caregivers show both satisfaction and dissatisfaction with the care provided, with the evolution of the PrU and with the support of external agents. CONCLUSION: The experience of informal caregivers of people with PrUs is based on 5 dimensions: (1) reasons to be caregivers, (2) care provided to the PrU, (3) impacts on the caregiver, (4) support to the caregiver, and (5) satisfaction or dissatisfaction of the caregiver.